2017
DOI: 10.1257/aer.p20171009
|View full text |Cite
|
Sign up to set email alerts
|

Gender Gap in High-Growth Ventures: Evidence from a University Venture Mentoring Program

Abstract: We track high-growth ventures from the idea stage to commercialization and investigate the nature of the gender gap early in the venture lifecycle. Using data on 651 venture ideas that collectively attracted over $700 million in venture financing, we find a significant gender gap among ventures without documented intellectual assets at the earliest stage of founding but not among ventures that already possess intellectual assets. We also find a gender gap in entrepreneurs' readiness to commit to their venture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Some startup founders handle these challenges by hiring experienced managers (Kulchina, ) or entering incubator or accelerator programs (Cohen & Hochberg, ). Most founders, however, likely rely on their own trial and error or on informal advice from peers and mentors (Lerner & Malmendier, ; Nanda & Sørensen, ; Scott & Shu, ). Prior work has conceptualized this advice as reflecting the adviser's own prior experience and knowledge (Lerner & Malmendier, ; Lindquist et al, ; Sørensen, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Some startup founders handle these challenges by hiring experienced managers (Kulchina, ) or entering incubator or accelerator programs (Cohen & Hochberg, ). Most founders, however, likely rely on their own trial and error or on informal advice from peers and mentors (Lerner & Malmendier, ; Nanda & Sørensen, ; Scott & Shu, ). Prior work has conceptualized this advice as reflecting the adviser's own prior experience and knowledge (Lerner & Malmendier, ; Lindquist et al, ; Sørensen, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Informal advice is distinct from coaching (Bryan et al, ), mentoring (Scott & Shu, ), and general feedback in a business‐plan competition (Clingingsmith & Shane, ; Howell, ). The advice that entrepreneurs seek out and receive (Vissa & Chacar, ) can be unstructured and highly dependent on the knowledge and experience of the adviser.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It has been observed that low self-efficacy is one of the barriers to women's engagement in more lucrative business industries (Wieland et al, 2019). However, when women in mentoring programs are fully committed to their ideas, they are likely to achieve similar results as their male counterparts especially in terms of venture financing and commercialization (Scott and Shu, 2017). Although this shows that men and women could benefit equally from entrepreneurial mentoring, it is more possible if all factors such as gender roles, access to resources, and social cultural constraints are kept constant for both males and females.…”
Section: Gender Differencesmentioning
confidence: 99%
“…There is a big gender gap in entrepreneurship ( Guzman and Kacperczyk, 2019 ). This is not only true regarding the number of women going into entrepreneurship but also in terms of success and persistence ( Smith and Tolbert, 2018 ; Oppedal and Garcia, 2019 ) and is more pronounced in high-growth ventures ( Scott and Shu, 2017 ). Moreover, even efforts to improve entrepreneurial outcomes tend to be more successful among men than women due to several constraints including time and low credit ( Oppedal and Garcia, 2019 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Between 2008 and 2020, the share of annual U.S. VC capital raised by female founders ranged between 1.7 percent and 2.7 percent, with no upward trend. 3 A growing literature, including Becker-Blease & Sohl (2007), Scott & Shu (2017), Gornall & Strebulaev (2018), and Ewens & Townsend (2019) has documented the gap in various ways, but has never directly addressed 1 The NVC is Harvard's flagship new venture competition and a key gateway to VC-backed entrepreneurship after HBS. Many successful founders, including those of 'unicorn' startups such as Rent the Runway and Oscar Health, have been participants in the NVC.…”
Section: Introductionmentioning
confidence: 99%